Beta secretase regulation and inflammation in pancreatic β-cells: the potential role of Rooibos - Burger, Joleen; Stellenbosch University. Faculty of Medicine and Health Sciences. Dept. of Biomedical Sciences. Anatomy and Histology. (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScMedSc)--Stellenbosch University, 2018.